Investigation of Electrically Evoked Auditory Brainstem Responses to Multi-Pulse Stimulation of High Frequency in Cochlear Implant Users - Saeedi, Ali; Hemmert, Werner (Frontiers in Neuroscience, 2020)
We investigated the effects of electric multi-pulse stimulation on electrically-evoked auditory brainstem responses (eABRs). Multi-pulses with a high burst rate of 10000 pps were assembled from pulses of 45 µs phase duration. Conditions of 1-, 2-, 4-, 8-, and 16-pulses were investigated. Psychophysical thresholds (THRs) and most comfortable levels (MCLs) in multi-pulse conditions were measured. Psychophysical temporal integration functions (slopes of THRs/MCLs as a function of number of pulses) were -1.30 and -0.93 dB/doubling of the number of pulses, which correspond to the doubling of pulse duration.A total of 15 eABR conditions with different number of pulses and amplitudes were measured. The morphology of eABRs to multi-pulse stimuli did not differ from those to conventional single-pulses. eABR wave eV amplitudes and latencies were analyzed extensively. At a fixed stimulation amplitude, increasing number of pulses caused increasing wave eV amplitudes up to a certain, subject-dependent number of pulses. Then amplitudes either saturated or even decreased. This was contradicting to the conventional amplitude growth functions and also contradicting to psychophysical results. We showed that destructive interference could be a possible reason for such a finding, where peaks and troughs of responses to the first pulses were suppressed by those of successive pulses in the train.This study provides data on psychophysical THRs and MCLs and corresponding eABR responses for stimulation with single pulses and multi-pulse stimuli with increasing duration. Therefore, it provides insights how pulse-trains integrate at the level of the brainstem.